(untitled) (Fountain Journal of Natural and Applied Sciences, 2021)
In vivo antitrypanosomal activity of 70% methanol extract of Tephrosia linearis was evaluated. Mice infected with Trypanosoma evansi in different groups were administered 100, 200, 300 and 400 mg/kg body weight/day of the seventy percent (v/v) (methanol/water) crude extract of T. linearis intraperitoneally. The positive control group was treated with standard drug, berenil, while the negative control was infected and treated with normal saline. Doses of 300 and 400 mg/kg bw i.p. per day were found to significantly reduce the parasite loads and sustained the animals in the respective groups up to 3 and 4 weeks beyond the experimental period. There is drop in the percentage PCV during the first six days of the treatment but this was reversed in the subsequent days, except in the negative control group. The animals administered the highest effective (trypanostatic) dose of 400 mg/kg body weight for five consecutive days prior to infection were observed to develop infection 72 h post inoculation. The LD50 determined was found to be 2800 mg/kg bw. It is obvious that, higher doses of 300 and 400 mg/kg bw has trypanostatic effect. Though, the extract could not show any prophylactic activity, further purification may possibly yield a fraction with trypanocidal effect. Keywords: Tephrosia linearis, Methanol extract, Trypanosoma evansi, Antitrypanosomal activity, In vivo